2018
DOI: 10.3390/ijms19030756
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Polyamine Biomarker Panels with Machine-Learning Differentiated Colorectal Cancers, Benign Disease, and Healthy Controls

Abstract: Colorectal cancer (CRC) is one of the most daunting diseases due to its increasing worldwide prevalence, which requires imperative development of minimally or non-invasive screening tests. Urinary polyamines have been reported as potential markers to detect CRC, and an accurate pattern recognition to differentiate CRC with early stage cases from healthy controls are needed. Here, we utilized liquid chromatography triple quadrupole mass spectrometry to profile seven kinds of polyamines, such as spermine and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
5
48
0
Order By: Relevance
“…Deng, Fang et al (2017) validated a biomarker panel that was suggested by H. Wang et al in 2014, and they found similarly high sensitivity [ 48 , 51 ]. N1, N12-Diacetylspermine was found to be an individual biomarker candidate by two different studies [ 47 , 56 ]. Performance indicators of urine and stool-based biomarker panels can be found in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Deng, Fang et al (2017) validated a biomarker panel that was suggested by H. Wang et al in 2014, and they found similarly high sensitivity [ 48 , 51 ]. N1, N12-Diacetylspermine was found to be an individual biomarker candidate by two different studies [ 47 , 56 ]. Performance indicators of urine and stool-based biomarker panels can be found in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, none of these biogenic amines were positively or negatively associated with genital inflammation. Arginine and its polyamine product N(1)-acetylspermine are indicative of rapidly proliferating cells [56] and positively correlated with Lactobacillus abundance and genital inflammation. Previously, arginine metabolism was previously highlighted as an emerging hallmark of cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…N 1 , N 12 -diacetylspermine has also been observed in high concentrations in biofilm-associated, right-side colon cancers 60,61 . Finally, polyamines and polyamine metabolites measured in either urine or serum have shown potential as biomarkers for prostate, colon and pancreatic cancers 6266 . Such analyses, combined with increasingly precise genomic signatures, may aid in the development of more personalized approaches to cancer diagnosis and treatment based on using polyamines as biomarkers.…”
Section: Polyamines and Cancermentioning
confidence: 99%